2021
DOI: 10.1002/ejic.202100349
|View full text |Cite
|
Sign up to set email alerts
|

Metal Cation‐Modified Graphene Oxide as Precursor for Advanced Materials: Thin Films of Graphene/Prussian Blue Analogues

Abstract: This work reports a simple, direct, and easy route to prepare thin films between graphene-like materials and two hexacyanometallates, based on metal cation modification in graphene oxide (GO) thin films obtained by the liquid/liquid interfacial route. The reaction between GO and Cu 2 + or Fe 3 + ions in aqueous solution yields GO/Cu 2 + or GO/Fe 3 + , and the nature of the interactions between the GO and the metal cations were demonstrated by FT-IR. GO/Cu 2 + and GO/Fe 3 + can be chemically reduced to reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Electrodeposition has the same controlled nucleation and growth effect but allows for a more varied composition (M sM ′ ), especially if the M source is immobilized in the electrode. [112][113][114] Electrodeposition can also orient the morphology 115 and create PBA composites with the electrode material, for example, carbon nanotubes 112 or graphene. 116 Layer-by-layer assembly is another method for controlled orientation of PBA particles while modifying the surface with potential active materials for derivatization, like polymers (for carbonization and conductivity), thiols or amides (for suldes or N-doped materials), or nanoparticles (for an additional metallic source and compositional complexity).…”
Section: Structure Design and Pbd Characteristicsmentioning
confidence: 99%
“…Electrodeposition has the same controlled nucleation and growth effect but allows for a more varied composition (M sM ′ ), especially if the M source is immobilized in the electrode. [112][113][114] Electrodeposition can also orient the morphology 115 and create PBA composites with the electrode material, for example, carbon nanotubes 112 or graphene. 116 Layer-by-layer assembly is another method for controlled orientation of PBA particles while modifying the surface with potential active materials for derivatization, like polymers (for carbonization and conductivity), thiols or amides (for suldes or N-doped materials), or nanoparticles (for an additional metallic source and compositional complexity).…”
Section: Structure Design and Pbd Characteristicsmentioning
confidence: 99%
“…[12] For GO, the following attribution was made at: i) 3420 and 1720 cm À 1 due to hydroxyls and carboxylic acids (C=O), respectively; ii) 1620 cm À 1 due to the non-oxidized graphitic domains (C=C) or adsorbed water; iii) discrete shoulder at 1283 cm À 1 and more intense band at 850 cm À 1 due to epoxides; iv) the several bands observed in the region of 1000-1250 cm À 1 are difficult to distinguish but are usually attributed to C-OH and CÀ O bonds of the oxygenated groups present (e. g. epoxide, hydroxyl, ketone). [12] Upon monofunctionalization via the epoxide groups, GOSH maintains some bands from GO but shows the decrease of the bands attributed to epoxides (1283 and 850 cm À 1 ), especially at 850 cm À 1 , [13] indicating the successful functionalization on the epoxide sites. In addition, the region of 1250-1000 cm À 1 shows a significant change in contrast to bare GO that can be due to the epoxide ring opening which generates new CÀ OH groups on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…As for the effect of potential on PB films, Baggio et al found that the morphology and structure of PB films depend on the deposition potential, and that thick, dense, and homogeneous high-quality PB was obtained in the limiting voltage interval of 0.30-0.22 V. [65] Ferreira et al pioneered the modification of graphene oxide (GO) with Cu 2 + and Fe 3 + , followed by reduction to redox graphene (rGO). [66] These four nanoparticle films were used as working electrodes and the corresponding G/PBAs was obtained by electrodeposition method. The prepared nanocomposites have the advantages of thinness, transparency and high uniformity.…”
Section: Electrodeposition Methodsmentioning
confidence: 99%
“…Ferreira et al. pioneered the modification of graphene oxide (GO) with Cu 2+ and Fe 3+ , followed by reduction to redox graphene (rGO) [66] . These four nanoparticle films were used as working electrodes and the corresponding G/PBAs was obtained by electrodeposition method.…”
Section: Synthesis Approachesmentioning
confidence: 99%